Microplastics in offshore sediment in the Yellow Sea and East China Sea, China. (January 2019) - Zhang, Chunfang; Zhou, Hanghai; Cui, Yaozong; Wang, Chunsheng; Li, Yanhong; Zhang, Dongdong
Abstract: Microplastic particles are a global concern due to their widespread and growing threat to marine and coastal environments. To improve knowledge of microplastic pollution in China, we investigated 25 sediment samples collected with a box corer in the Southern Yellow Sea and East China Sea off the coast of China. The microplastics were extracted from sediments via density separation, after which they were observed under a microscope and characterized according to shape, color, and size, while polymer type identification was performed using micro-Fourier transform infrared spectroscopy. The abundance of microplastics in the offshore region of the Southern Yellow Sea and East China Sea was mapped. The mean concentration of microplastics at the 25 sites was 13.4 ± 0.6 particles 100 g −1 dry weight (range: 6.0–24.0 particles 100 g −1 dry weight). Based on the categorization according to shape, color, and size, fiber (77%) was the most abundant shape, while blue (35%) and transparent (29%) were the most prevalent colors. In addition, the dominant size of microplastics was smaller than 1000 μm which accounted for 89%. Finally, polyethylene, polyethylene terephthalate, acrylic, polyester, cellulose, and cellophane were the most abundant types of microplastics identified. Our result highlighted the presence of microplastics in offshore sediments from the Yellow Sea and East China Sea, and provided useful information for evaluating the environmental risks posed by microplastics in China. Graphical abstract: Image 1 Highlights: Microplastic pollution in offshore sediments from China was reported. Abundance was correlated with site distance and grain size distribution. Microplastics <1000 μm were the predominant size, accounting for 89%. Cellophane and PET were the most common types of microplastic polymers. This study offers useful data on microplastic pollution in offshore areas of China. Abstract : We clarified the state of microplastic particles, as ubiquitous and potentially toxic pollutants, in sediments off the coast of China.